The safety and efficacy of feracrylum as compared to silver sulfadiazine in the management of deep partial thickness burn: A clinical study report (Medical Journal of Indonesia, 2008)
Instead of haemostatic effect, feracrylum provides antibacterial activity; wound improvement has been clinically proven. Feracrylum is a water soluble mixture of incomplete ferrous salt of polyacrylic acid containing 0.05 to 0.5% of iron in physiologic solution (0.85% solution of sodium chloride). A clinical study on safety and efficacy of feracrylum compared to silver sulfadiazine (SSD) was conducted in burn management, since with the widely use of SSD, the sulfadiazine's disadvantages lead to wound healing impairment. In this open, randomized, controlled study, feracrylum and SSD were topically applied, each on different side of the burnt areas in parts of body for a treatment period of eleven days. Of eight enrolled patients, seven patients completed the study; one patient withdrew due to acute burn complication. On day 7th and 11th, the re-epithelialization in group receiving feracrylum increased as the raw surface area reduced. Mean percentages of epithelialization on both evaluation days in Feracrylum group were 70.53±24.298 and 81.71±28.922, respectively, which were higher than SSD group (66.15±25.080 and 64.64±74.684 respectively). Feracrylum was found to be safe and well tolerated. This study showed a clinical difference although it was not significant statistically. (Med J Indones 2008; 17: 259-71)